BANK PERKREDITAN RAKYAT PILIHAN NASABAH SAAT PANDEMI COVID-19 - I Nyoman Nugraha Ardhana Putra; Budi Santoso; Lilik Handajani (JMM UNRAM - MASTER OF MANAGEMENT JOURNAL, 2022)
This study aimed to analyze the differences in profitability and operational efficiency before and during the COVID-19 pandemic in rural banks. It is interesting, and when all industries experience a decline, BPRs can still survive by posting positive profits. This quantitative research with a comparative research type compares the profitability and efficiency of Rural Banks (BPR) in West Nusa Tenggara before and during the pandemic. The output is essential in providing model recommendations so that BPRs in NTB survive during a pandemic and can continuously serve the community and MSMEs in alleviating poverty according to the leading areas of poverty alleviation and the top topic of the study of capital schemes. The research location is at Rural Banks in West Nusa Tenggara (NTB) Province from the end of 2019 to mid-2020. The analytical tool used is the t-test (differentiation test) of 2 paired samples. This research shows the ability of BPRs to survive and generate profits during a pandemic. Key Words: Profitability, Efficiency, Pandemic Covid-19 and Rural Banks.